Microbiome-based therapeutics for metabolic disorders: harnessing microbial intrusions for treatment - Ahmed, Nafees; Gaur, Vishwas; Kamle, Madhu; Chauhan, Abhishek; Chauhan, Ritu; Kumar, Pradeep; Singh, Namita Ashish (Frontiers in Medical Technology, 2025)
The rising global rates of metabolic disorders, such as obesity, type 2 diabetes, non-alcoholic fatty liver disease, and metabolic syndrome, call for new treatment methods beyond traditional drugs. The human gut microbiota, made up of trillions of microorganisms that plays a crucial role in maintaining metabolic balance through complex biochemical processes and interactions between hosts and microbes. Dysbiosis, which involves changes in microbial composition and a decrease in diversity, has become a major factor in metabolic problems. This disruption impacts the production of short-chain fatty acid, increase in permeability of intestine, and causes enduring low-grade inflammation. This review features into the potential of treatments based on microbiome for metabolic syndromes, focusing on probiotics, prebiotics, synbiotics, and postbiotics. It also encompasses innovative methods such as engineered microbial consortium, fecal microbiota transplantation (FMT), and vaginal microbiota transplantation (VMT). Probiotics show significant promise in improving blood sugar control and enhancing lipid levels. Prebiotics help bring about positive changes in microbial composition and the production of beneficial metabolites. Synbiotic combinations provide added benefits by helping good microbes thrive while supplying nutrients they can ferment. Postbiotics have recent research focus because they are safer, more stable, easier to store, and less likely to contribute to antibiotic resistance comparative to live probiotics. Even now there are substantial complications in translating microbiome research into standardized therapeutics despite of promising pre-clinical outcomes and some initial clinical data. These comprises individual variances, strain-specificity, dosage problems, regulation issues, and the necessity for personalised treatment strategies. Future success will depend upon personalized medicine, technological developments, and the incorporation of multi-omics strategy to generate metabolic health therapeutics depending on targeted microbiomes.